XERODERMA PIGMENTOSA WITH MULTIPLE CUTANEOUS MALIGNANCIES– A RARE CASE REPORT AND REVIEW OF LITERATURE - Shetty, Rohan; S., Girish B.; Ballal, Rajesh; Permi, Harish S.; Makannavar, Pramodh; Alva, Vinay (Journal of Health and Allied Sciences NU, 2013)
Xeroderma pigmentosa is a rare autosomal recessive disorder, characterized by photosensitivity, pigmentary changes, premature skin aging, and marked increase in risk of developing malignant neoplasms of the skin and eyes. Here we present a 13 year old girl with xeroderma pigmentosa who developed multiple cutaneous malignancies in the face and upper limb.
Keywords: Xeroderma pigmentosa; multiple skin cancer; squamous cell carcinoma; basal cell carcinoma